1999
DOI: 10.1097/00132586-199902000-00059
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Adverse Drug Reactions in Hospitalized Patients: A Meta-Analysis of Prospective Studies

Abstract: Objective.-To estimate the incidence of serious and fatal adverse drug reactions (ADR) in hospital patients.Data Sources.-Four electronic databases were searched from 1966 to 1996. Study Selection.-Of 153, we selected 39 prospective studies from US hospitals.Data Extraction.-Data extracted independently by 2 investigators were analyzed by a random-effects model. To obtain the overall incidence of ADRs in hospitalized patients, we combined the incidence of ADRs occurring while in the hospital plus the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
1,572
11
147

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,394 publications
(1,777 citation statements)
references
References 0 publications
42
1,572
11
147
Order By: Relevance
“…[1][2][3][4] Black box warnings (BBWs) are the strongest medication-related safety warnings that can be placed in a drug's labeling information according to the Food and Drug Administration (FDA) 5 and highlight major drug-related risks. 6 Based on evidence from animal, clinical, or post-marketing surveillance studies and reports, the FDA decides whether acquisition and/or updating of a BBW is required.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Black box warnings (BBWs) are the strongest medication-related safety warnings that can be placed in a drug's labeling information according to the Food and Drug Administration (FDA) 5 and highlight major drug-related risks. 6 Based on evidence from animal, clinical, or post-marketing surveillance studies and reports, the FDA decides whether acquisition and/or updating of a BBW is required.…”
Section: Introductionmentioning
confidence: 99%
“…3 During 1994, ADRs affected over 2 million people in the United States, resulting in over 100 000 deaths. 4 In 2002, ADRs accounted for 6.5% of hospital admissions and 0.15% of subsequent deaths in the United Kingdom. 5 Thus, patients, the medical community, health-care providers, regulatory agencies and the pharmaceutical industry have a compelling interest to identify factors that influence ADR risk.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of these errors involve medi- cations. A meta-analysis of 39 prospective studies indicated that adverse drug reactions may rank between the fourth and seventh leading cause of deaths in the U.S. [3]. One study of medication errors in 36 hospitals and skilled nursing facilities in Georgia and Colorado found that 19% of the doses were in error; 7% of the errors could have resulted in adverse drug events [4].…”
Section: Introductionmentioning
confidence: 99%